Immunohistochemical markers for histopathological diagnosis and differentiation of acute cutaneous graft‐versus‐host disease. Issue 12 (5th July 2021) - Wegner, Joanna; Weidenthaler‐Barth, Beate; Engelbert, Julia; Knothe, Max; Braun, Claudia; Helbig, Doris; Sacher, Christopher; Kreft, Andreas; Wagner, Eva M.; Ziemer, Mirjana; Meyer, Ralf G.; von Stebut, Esther
Abstract: Graft‐versus‐host disease (GvHD) is a major complication following stem‐cell or solid‐organ transplantation. Accurate diagnosis of cutaneous GvHD is challenging, given that drug eruptions and viral rashes may present with similar clinical/histological manifestations. Specific markers are not available. We performed the histological examination of biopsy samples from acute GvHD (aGvHD; n = 54), Stevens‐Johnson syndrome/toxic epidermal necrolysis (SJS/TEN; n = 27), maculopapular drug eruption (MDE; n = 26) and healthy controls ( n = 26). Samples of aGvHD showed a decrease in Langerhans cells (LC, p = 0.0001) and an increase in macrophages (MΦ, p = 0.0001) compared to healthy skin. Compared to SJS/TEN, MDE and healthy skin, aGvHD biopsies contained greater numbers of CD4 + and CD8 + T cells. The majority of CD4 + T‐helper cells were localized in the upper dermis, whereas cytotoxic CD8 + T cells were found in the epidermis. Increased numbers of CD56 + natural killer (NK) cells in the upper dermis of aGvHD skin ( p = 0.007) were not observed in controls or SJS/TEN and MDE. There were no differences in elafin staining between aGvHD and the latter two conditions. Acute GvHD appears to have a distinct inflammatory cell profile (T cells/NK cells) that may aid establishing in a more accurate diagnosis, especially when used to rule out differential diagnoses such as SJS/TEN or MDE.